Achievement of Students' Mathematical Understanding Through ICT-Assisted Analytical Geometry Learning - Sudihartinih, Eyus; Ghaida, Silmi; Pebrianti, Aneu (FKIP Universitas Lampung, 2025)
Analytical geometry is a crucial component of the curriculum for prospective mathematics teacher education, as it serves as a foundational skill for teaching in schools. However, recent studies have revealed that some students possess a limited comprehension of analytical geometry. In the current era, characterized by rapid technological advancement, there is an imperative for innovation in the pedagogy of analytical geometry, including the integration of ICT. This study aims to describe ICT-assisted analytical geometry learning and learning outcomes in the form of students' mathematical understanding achievements. The present study employs a mixed methods approach, integrating a sequential explanatory design. The quantitative research design employed is descriptive in nature, as it aims to articulate the students' mathematical understanding. To enhance the comprehension of the quantitative findings, qualitative research was conducted employing a holistic case study design, enabling a more profound examination of the data by incorporating students' perspectives and interpretations. The population of this study comprised second-semester prospective teacher students in classes A and B who had enrolled in analytical geometry courses at a university in Bandung City, Indonesia. The sample of this study was selected by purposive sampling, namely class A with a total of 40 students (12 males and 28 females). The study's findings suggest that the incorporation of ICT, specifically GeoGebra software and e-learning, enhances the effectiveness of learning analytical geometry, particularly the plane geometry topic. This enhancement is evident in the students' achievement in terms of mathematical understanding, which is satisfactory. Consequently, it is imperative to extend the application of ICT to other subjects or instructional segments. Keywords: ICT, geogebra, analytical geometry.